Unpacking the Shortcomings of "College and Career Readiness" as an Educative Approach in Urban Schools as Preparation for Tomorrow's Economy - Keith E. Benson; Leah Z. Owens (MDPI AG, 2022)
As the language of "college and career readiness" continues to permeate American public education, the fixation on preparing students for college and careers is potentially harmful for students, particularly urban students of color. In promoting "college and career readiness", certain assumptions are taken for granted: that American schools are sites of egalitarian meritocracy and not spaces of social reproduction; that tomorrow's job market desires more individuals with formal education, and that the jobs market will be viable for tomorrow's willing workers. Here, we argue that as "college and career readiness" continues to be the dominant approach in American schools, it ignores the realities that the workplace of tomorrow is growing harsher as corporations continue their efforts to maximize profits by keeping labor costs low by reducing worker participation and seeking cheaper labor. Simultaneously, American students of color are more vulnerable to tomorrow's workplace in that they continue to experience racial discrimination coupled with the growing tenuous nature of the future domestic job market. Thus, students who are being schooled in "college and career readiness" have to contend with the possibility that, though they are more formally educated, the economy of tomorrow may still deem them expendable.